Das ondas do rádio à teia da rede: Podcast Café Brasil - Yoshimoto, Eduardo (2014)
From the transmission of culture through orality to the new digital communication technologies, human beings have made themselves present through the use of speech leaving marks in the world. This work deals with reading practices in a type of digital format: the podcast. These audio devices can be easily produced by anyone by viewing the tutorials available in cyberspace and distributed in episodes through the Internet. The effects of discursive practices and meanings mobilized through listening of the aforementioned device are seized at alternative times and spaces. Timing and place can be chosen by the listener when it best suits him or her, unlike the radio era when, once the program had passed, he could not be heard because the listener had no control of the programming. Furthermore, this new device offers the listener the possibility of use while performing other tasks. The interest of studying the discursive and reading practices on mobile devices, which also serve as support for the podcast, should to the fact that most children and teenagers attending the basic education system nowadays use tools like mobile phones, MP3 players, tablets and other gadgets to read informally, both as a means of information and as a means of entertainment. This offers a great potential for use in education. This study aims at analyzing the discursive and audio reading practices mobilized in the Cafe Brazil Podcast, and the sensory effects the reading by listening to this device engender in his listeners, especifically the discourse analysis in the comments section of the site and its potential for education. The corpus of this analysis consists of three episodes produced by the website Café Brazil, selected from the period between 2012 and 2013, from the following categories: a commemorative and historical landmark theme of the program, a theme linked to education and the last issue is a response to criticism of one of the listeners. The theoretical and methodological framework is based on discourse analysis of French origins. The speech genres are based on Bakhtin and Maingueneau, and radio genres based on Barbosa Filho. The contextualization and overview of the socio-historical moment of postmodernity is supported by Bauman’s concept of "liquidity". In relation to the podcast, it works with educational technology proposed by Carvalho Aguiar. The object of this study resumes the practice of oral and listening practices reinserting them, via technological means, as an instrument of the subjectivity of the world, and as a result the acquisition of elements for a discursive practice different from the traditional and conservative school practices. This presents a dynamic, fluid and fun way for many young people, in addition to being a consumer reading for what is currently in the media. It can be used within and outside schools as an ally to an education in which reading is no longer just the consumption of information or entertainment, but the opportunity to access different ways of reading. Keywords: reading practices; genres; podcast; education.